Enhanced integration of large DNA into E. coli chromosome by CRISPR/Cas9. Issue 1 (5th August 2016) - Chung, Mu‐En; Yeh, I‐Hsin; Sung, Li‐Yu; Wu, Meng‐Ying; Chao, Yun‐Peng; Ng, I‐Son; Hu, Yu‐Chen
ABSTRACT: Metabolic engineering often necessitates chromosomal integration of multiple genes but integration of large genes into Escherichia coli remains difficult. CRISPR/Cas9 is an RNA‐guided system which enables site‐specific induction of double strand break (DSB) and programmable genome editing. Here, we hypothesized that CRISPR/Cas9‐triggered DSB could enhance homologous recombination and augment integration of large DNA into E. coli chromosome. We demonstrated that CRISPR/Cas9 system was able to trigger DSB in >98% of cells, leading to subsequent cell death, and identified that mutagenic SOS response played roles in the cell survival. By optimizing experimental conditions and combining the λ‐Red proteins and linear dsDNA, CRISPR/Cas9‐induced DSB enabled homologous recombination of the donor DNA and replacement of lac Z gene in the MG1655 strain at efficiencies up to 99%, and allowed high fidelity, scarless integration of 2.4, 3.9, 5.4, and 7.0 kb DNA at efficiencies approaching 91%, 92%, 71%, and 61%, respectively. The CRISPR/Cas9‐assisted gene integration also functioned in different E. coli strains including BL21 (DE3) and W albeit at different efficiencies. Taken together, our methodology facilitated precise integration of dsDNA as large as 7 kb into E. coli with efficiencies exceeding 60%, thus significantly ameliorating the editing efficiency and overcoming the size limit of integration using the commonly adopted recombineering approach. Biotechnol. Bioeng. 2017;114: 172–183. © 2016 Wiley Periodicals, Inc. Abstract : Hu and colleagues employ the CRISPR/Cas9 system and optimize the experimental conditions to effectively induce double strand break at the target site of E. coli chromosome and integrate a donor DNA as large as 7 kb into the chromosome at an efficiency exceeding 60%.